Rare case of lingual thyroglossal cyst presenting in infant with respiratory distress - Saurabh Maheshwari; Pankaj Agarwal; Alok Tripathi; Karan Raheja; Rachit Goel; Sachin Dubey (Journal of Pediatric Critical Care, 2022)
Thyroglossal duct cyst (TDC) is the most common congenital anomaly of the neck. The thyroglossal duct is an embryological structure which connects the base of the tongue to the thyroid gland, which when fails to obliterate results in this anomaly. The incidence of this anomaly is approximately 7%, representing about 75% of the congenital masses of the neck. This cystic lesion is usually mobile and nontender in nature and usually presents with respiratory distress in infants. A lingual TDC is the rarest form of a TDC, and differs from a classical thyroglossal cyst totally in presentation and management. We present here a rare case of 2-month infant presenting with respiratory distress due to lingual TDC extending up to the suprathyroid region.